Analisis Strategi Hedging untuk Manajemen Risiko Optimal pada Perbankan - Fia Dialysa (Lembaga Pengembangan Kinerja Dosen, 2024)
Hedging is a financial instrument that uses a risk management approach to neutralize systematic risk against changes in prices or cash flows: individuals and businesses. One alternative that can be done to minimize this risk of banking is hedging. (Hasanah, 2022). This study analyzes hedging strategies to achieve optimal risk management in banking companies. The object of the study is the banking industry, both conventional and sharia, listed on the IDX with an observation period of 2019-2023. The targeted outputs are scientific publications and national journals. The results of the study are Hedging strategies: (1) Forward Contract, (2) Futures Contract, and (3) Money Market. Hedging strategy implementation techniques are (1) Arbitrage (2) Diversification (3) Average down (4) Cash closing.